Hypothalamic Leptin Gene Therapy Reduces Bone Marrow Adiposity in ob/ob Mice Fed Regular and High-Fat Diets - Lindenmaier, Laurence B.; Philbrick, Kenneth A.; Branscum, Adam J.; Kalra, Satya P.; Turner, Russell T.; Iwaniec, Urszula T. (Frontiers in Endocrinology, 2016)
Low bone mass is often associated with elevated bone marrow adiposity. Since osteoblasts and adipocytes are derived from the same mesenchymal stem cell (MSC) progenitor, adipocyte formation may increase at the expense of osteoblast formation. Leptin is an adipocyte-derived hormone known to regulate energy and bone metabolism. Leptin deficiency and high-fat diet-induced obesity are associated with increased marrow adipose tissue (MAT) and reduced bone formation. Short-duration studies suggest that leptin treatment reduces MAT and increases bone formation in leptin-deficient ob/ob mice fed a regular diet. Here, we determined the long-duration impact of increased hypothalamic leptin on marrow adipocytes and osteoblasts in ob/ob mice following recombinant adeno-associated virus (rAAV) gene therapy. Eight- to 10-week-old male ob/ob mice were randomized into four groups: (1) untreated, (2) rAAV-Lep, (3) rAAV-green fluorescent protein (rAAV-GFP), or (4) pair-fed to rAAV-Lep. For vector administration, mice were injected intracerebroventricularly with either rAAV-leptin gene therapy (rAAV-Lep) or rAAV-GFP (9 × 107 particles) and maintained for 30 weeks. In a second study, the impact of increased hypothalamic leptin levels on MAT was determined in mice fed high-fat diets; ob/ob mice were randomized into two groups and treated with either rAAV-Lep or rAAV-GFP. At 7 weeks post-vector administration, half the mice in each group were switched to a high-fat diet for 8 weeks. Wild-type (WT) controls included age-matched mice fed regular or high-fat diet. High-fat diet resulted in a threefold increase in MAT in WT mice, whereas MAT was increased by leptin deficiency up to 50-fold. Hypothalamic leptin gene therapy increased osteoblast perimeter and osteoclast perimeter with minor change in cancellous bone architecture. The gene therapy decreased MAT levels in ob/ob mice fed regular or high-fat diet to values similar to WT mice fed regular diet. These findings suggest that leptin plays an important role in regulating the differentiation of MSCs to adipocytes and osteoblasts, a process that may be dysregulated by high-fat diet. However, the results also illustrate that reducing MAT by increasing leptin levels does not necessarily result in increased bone mass.